2000
DOI: 10.4049/jimmunol.164.11.5913
|View full text |Cite
|
Sign up to set email alerts
|

CD40 Ligand (CD154) Enhances the Th1 and Antibody Responses to Respiratory Syncytial Virus in the BALB/c Mouse

Abstract: CD40 ligand (CD40L) is a cell surface costimulatory molecule expressed mainly by activated T cells. CD40L is critically important for T-B cell and T cell-dendritic cell interactions. CD40L expression promotes Th1 cytokine responses to protein Ags and is responsible for Ig isotype switching in B cells. Respiratory syncytial virus (RSV) is an important pathogen of young children and the elderly, which causes bronchiolitis and pneumonia. Studies of mice infected with RSV suggest that a Th2 cytokine response may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
29
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 67 publications
2
29
1
Order By: Relevance
“…CD40L chimeric SIV VLPs were very efficient in stimulating robust CD4 ϩ -and CD8 ϩ -T-cell responses. Our findings on the induction of T-cell responses by CD40L are consistent with previously published studies (32,46,49). However, CD40L SIV VLPs did not induce enhanced SIV-Env specific serum IgG levels even after three immunizations; the levels were comparable to those found with control SIV VLPs.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…CD40L chimeric SIV VLPs were very efficient in stimulating robust CD4 ϩ -and CD8 ϩ -T-cell responses. Our findings on the induction of T-cell responses by CD40L are consistent with previously published studies (32,46,49). However, CD40L SIV VLPs did not induce enhanced SIV-Env specific serum IgG levels even after three immunizations; the levels were comparable to those found with control SIV VLPs.…”
Section: Discussionsupporting
confidence: 82%
“…Another immunostimulatory molecule is CD40 ligand (CD40L), which is a surface molecule primarily expressed on mature CD4 ϩ T cells. Interaction between CD40L and CD40 is important for T-cell-dependent B-cell activation and isotype switching (5,49). Binding of CD40L to CD40 modulates the cellular immune responses by inducing interleukin 12 (IL-12) production and expression of costimulatory molecules residing on antigen-presenting cells (APCs).…”
mentioning
confidence: 99%
“…Studies using CD154-deficient mice or various autoimmune, infection, and transplant models have shown that CD40-mediated costimulation is involved in both type 1 and type 2 responses. However, results concerning the particular requirement for CD40-mediated costimulation in both responses are contradictory (7,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24).…”
mentioning
confidence: 99%
“…Blocking of CD154 in NOD/shi mice also impaired the development of isletreactive Th1 cells (7). Moreover, the CD40-CD154 interaction was demonstrated to be crucial for in vivo priming of Th1 cells by IL-12-producing APC in SJL/J mice (21), and supplementary expression of CD154 directs the response to respiratory syncytial virus toward a type 1 phenotype (22). At last, anti-CD154 Ab was found to induce tolerance to 2,4-dinitrofluorobenzene-induced contact hypersensitivity, a typical type 1 phenomenon (23), but CD154-deficient mice showed normal delayed-type hypersensitivity responses to OVA (24).…”
mentioning
confidence: 99%
“…The expression of CD154 appeared to enhance both immune responses and disease protection (Mendoza et al, 1997, Gurunathan et al, 1998, Tripp et al, 2000. Some studies have shown that co administration of plasmid encoded bovine CD154 enhanced antibody responses to bovine herpesvirus I glycoprotein D in sheep (Manoj et al, 2003).…”
Section: Discussionmentioning
confidence: 99%